Protection of the Economic Rights of the Licensee for the Activities of Watching Together Without Permission - Muhamad Akmal Jamalullail; Irvan Fauzan; Harmono; Moh Sigit Gunawan (PT FORMOSA CENDEKIA GLOBAL, 2025)
Economic rights in the Copyright Law Number 28 of 2014 expressly protect the potential income from cinematographic works, including football broadcasts. The practice of illegal watching, especially commercial ones, directly violates the exclusive rights of copyright owners and broadcasting rights to economically utilize their works through performances and communication to the public. Football broadcasts as cinematographic works are protected by copyright, and commercial broadcasting without a permit violates the economic rights of the creator/copyright holder and broadcasting rights, potentially subject to criminal sanctions and/or fines. The protection of the financial rights of the broadcasting rights licensee is based on exclusive rights.The research uses a normative juridical method by examining Law Number 28 of 2014, finding that various regulations regulate the enforcement of economic rights violations. To protect the economic rights of football broadcasters from illegal piracy, strategic steps include raising public and business awareness of economic losses due to copyright infringement, firm and consistent law enforcement, providing legal piracy solutions through affordable commercial licensing schemes, and strengthening international cooperation to eradicate cross-border piracy.